Immune therapy in inflammatory bowel disease and models of colitis. - Singh, B; Powrie, F; Mortensen, N (2001)
BACKGROUND: A proliferation of animal models has not only improved our understanding of inflammatory bowel disease, it has also formed the basis of new treatment strategies. METHODS: A search was conducted using the National Library of Medicine for articles discussing immune therapies for inflammatory bowel disease. This was supplemented by findings from the authors' own laboratory. RESULTS: An overview of the different animal models is presented. These models are used to highlight the recent human trials of immune therapies. Potential future therapies are also discussed. CONCLUSION: Immune therapies have altered the management of patients with inflammatory bowel disease. In future they will influence not only the indications for surgery but also its timing and outcome.